Plaidoyer pour une émergence de l’économie fondée sur la connaissance (EFC) dans les Pays Africains: Advocacy for the emergence of the knowledge-based economy (KFE) in African countries - Djamel torqui GODIH; Mohammed LAZREG (Journal of North African Economies, 2025)
The wealth of nations is increasingly based on the knowledge and skills of their labor force. The knowledge-based economy (KBE) is part of a long movement of transformation of world economies. EFC is a lever of action that gives a country many competitive advantages. Also, the central objective of our paper is to highlight that: EFC is the Achilles heel for the emergence of African economies. Thus, all the means of sensitizing African societies must be mobilized within this framework. For an effective realization of the EFC certain fundamental levers must be implemented.